Randomized Prospective Evaluation of Microblepharoexfoliation BlephEx as Adjunctive Therapy in the Treatment of Chalazia. Issue 2 (6th February 2023) - Zhu, Daniel; Gupta, Rohun R.; Stein, Rebecca L.; Quintero, Jose; Morcos, Marcelle M.; Link, Timothy J.; Perry, Henry D.
Abstract : Purpose: Chalazia are benign eyelid lesions caused by the obstruction and inflammatory reaction of the meibomian glands. Demodex mites are one potential cause of chalazia leading to mechanical obstruction of the meibomian gland. In this prospective randomized study, we examine a novel approach to treating chalazia with the use of microblepharoexfoliation (MBE), an in-office lid hygiene technique that exfoliates the eyelid margins. Methods: Fifty patients with clinical evidence of acute chalazion were enrolled in this study. Subjects were randomly assigned to a MBE plus lid hygiene group (23 patients, mean age 66.6 ± 16.6 years) or a lid hygiene alone group (27 patients, mean age 62.1 ± 14.4). The MBE plus lid hygiene group received MBE treatment and were evaluated 1 month after the baseline visit. The main outcome measured was the resolution of the chalazion at the 1-month follow-up visit. Results: The lid hygiene plus MBE treatment group demonstrated a statistically significant resolution of the chalazion compared with the lid hygiene group alone ( P = 0.007; chi-square test). Among the MBE plus hygiene group, 87% of the patients had resolution of their chalazion as opposed to the lid hygiene alone group, which had 44% resolution. Conclusions: This is the first prospective, randomized clinical trial that demonstrated efficacy of MBE as a noninvasive adjunctive treatment method for chalazion resolution.